Ikääntyneiden henkilöiden itsearvioidun stressinhallintakyvyn muutos ja siihen yhteydessä olevia tekijöitä koronaviruspandemian aikana - Ellonen, Anna (2024)
Stress-coping ability can be defined as an individual's ability to manage the adversities they face. Stress-coping ability plays an important role in old age, as ageing increases the risk of stressors and reduces the ability to recover from stressors. Older adults represent the most vulnerable risk group for the coronavirus pandemic that started in 2019. Despite this, there is very limited comparative longitudinal research on the self-rated stress-coping ability of older adults during the coronavirus pandemic. The aim of this study was to investigate whether older adults’ self-rated stress-coping ability changed during the coronavirus pandemic compared to the period before its onset. In addition, sex, age, perceived health, and perceived life satisfaction were examined in relation to changes in self-rated stress-coping ability.